Assessment of municipal water quality from water treatment plants in Selangor - Rwoo, Manutha Appa
From the pa t until present there are everal water epidemics of waterborne diseases caused by inefficient water treatment system. The increase in population growth and rapid urbanization has imposed a high impact on the global municipal water resources. Therefore, water security is a concern in the present. Eventhough the government has introduced the Environm ntal Quality Act (EQA) in 1974, the water quality in Malaysia is still deteriorating. The main pollution factors are the point source and non-point source in the water bodies. The study classified the quality of municipal water supply using multivariate health risk assessment and technique for biochemical and heavy metal parameter at 28 water treatment plants in Selangor from 2009 to 2012. Health risk assessment (mg/kg/day) for the 7 heavy metals was conducted by calculating the Hazard Quotient indexes for infants, children and adult categories. HACA, DA and PCA has been used to classify the water treatment plants to obtain the clearest picture of the municipal water supply status. Health risk assessment (mg/kg day) for heavy metal content in treated municipal water indicates selenium is at the boundary of higher risk levels for infants at 0.80 mg/kg/day level, but a potential risk for children and adults at 1.40 mg/kg/day level and 6.40 mg/kg/day. Zinc concentrations indicate a high risk of exposure for infants, children and adult at I.S7mg/kg/ day, 2.84mg/kg/day and 62.20mg/kg/day for zinc. HACA grouped the 28 monitoring tation into three different clusters based on their similarities namely good municipal water water quality (GMWQ), medium municipal water quality (MMWQ) and low municipal water quality (LMWQ). The 31 water quality parameter for treated water (TC, Turbidity, Colour, pH, Temperature, TDS, Residual CI, Cl, NH3- , N03- , Fe, F, Hardness, At, Mn, Hg,